A more intuitive way to post figure skating scores (and why Sotnikova deserved to win) - Stefani, R. (Significance, 2014)
I will suggest a much more intuitive way to post the scores, without any change to the system itself. I will illustrate my proposal using a cause célèbre at Sochi. Adelina Sotnikova (Russia) won gold in the women`s figure skating, outscoring Yuma Kim (Korea). Opaqueness made the scoring system its own worst enemy. The three medal winners` scores appear at the top portion of Table 1, just as the public saw them after the free skate. The 'Technical Element' score for Sotnikova is higher than for Kim; but why was it higher? The two had similar 'Program Component' scores, although the public probably does not understand what that score entails. When combined with the previous short program score (where the Russian had a deficit of 0.28 points), Sotnikova finished 5.48 points clear for the gold medal.